Pathogenesis of Insulin Resistance in Skeletal Muscle - Abdul-Ghani, Muhammad A. (Hindawi Publishing Corporation, 2010)
Insulin resistance in skeletal muscle is manifested by decreased insulin-stimulated glucose uptake and results from impaired insulin signaling and multiple post-receptor intracellular defects including impaired glucose transport, glucose phosphorylation, and reduced glucose oxidation and glycogen synthesis. Insulin resistance is a core defect in type 2 diabetes, it is also associated with obesity and the metabolic syndrome. Dysregulation of fatty acid metabolism plays a pivotal role in the pathogenesis of insulin resistance in skeletal muscle. Recent studies have reported a mitochondrial defect in oxidative phosphorylation in skeletal muscle in variety of insulin resistant states. In this review, we summarize the cellular and molecular defects that contribute to the development of insulin resistance in skeletal muscle.